PERLINDUNGAN HUKUM TERHADAP PEJABAT PEMBUAT KOMITMEN (PPK) DALAM PENGADAAN BARANG/JASA PEMERINTAH PADA SISTEM PENGADAAN SECARA ELEKTRONIK - Mita Kristiani (Legal Spirit, 2020)
Legal protection or legal assistance for government procurement of goods services is actually regulated  in relevant laws and regulations, but what kind of protection has not been explained and regulated in detail in the laws and regulations. Due to the absence of a rule that regulates explicitly and clearly related to the protection of actors in the procurement of government goods/services and the lack of attention from the government. So based on this, the thing offered is the need to make a policy that regulates clearly and completely related to the protection of government procurement of goods/services.Keywords: Procurement of Government Services, Commitment Making Officer, Legal protection